Mispricing Explanations of Closed-End Funds: A Survey Review - Stylianos X. Koufadakis (SPOUDAI - Journal of Economics and Business, 2016)
The aim of this survey is to review the most prevailing developments regarding the existence of the closed-end funds' discounts and premiums and the factors which generate them. Despite the plethora of academic research conducted in order to reach a generally accepted explanation of the closed-end fund puzzle based on both the traditional and the behavioral approaches, particular attention is still required to be payed to the pricing of closed-end funds in the academic literature to date. As the divergence between the closed-fund market prices and their fundamental values offers great challenges to a possible interpretation, this study summarizes a set of conclusions that can help researchers and practitioners study better this financial asset category. This paper is organized as follows: Section 1 summarizes the basic reference for closed-end funds; Section 2 captures the different theories on the existence of closed-end fund puzzle; Section 3 analyzes the theories of discount according to the main traditional interpretations; Section 4 reviews the explanation of discounts taking into account the investor behavior arguments; Section 5 deals with closed-end funds in the international financial environment; and Section 6 provides the conclusions.
Keywords: G10; G12; G20; 330; Closed-end funds; discounts/premiums